Bilateral Breast Cancer in a 65-Year-Old Man - Sharbatdaran, Arman; Twam, Mohammed; Nikbakhsh, Novin; Ghorbane, Hosseine (Archives of Clinical and Medical Case Reports, 2022)
Globally, breast cancer in men is exceedingly uncommon. The misinterpretation of signs and symptoms and lack of a proper medical history can lead to the progression of rare conditions to advanced stages. We report the case of a 65-year-old man who presented to the clinic complaining about progressive bilateral dull breast pain. He had been diagnosed with bilateral grade II invasive ductal carcinoma three months prior, and he underwent bilateral mastectomy followed by chemotherapy as a part of his treatment plan.